2015
DOI: 10.1016/j.ejvs.2014.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Detergent Sclerosants are Deactivated and Consumed by Circulating Blood Cells

Abstract: Detergent sclerosants are consumed and deactivated by circulating blood cells. This deactivating effect is above and beyond the neutralizing effects of plasma proteins and contributes to the overall neutralizing effect of blood. Different blood cell types exhibited varying levels of vulnerability to the lytic activity of sclerosants with platelets being the most and erythrocytes the least vulnerable (platelets > leukocytes > erythrocytes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 12 publications
0
37
0
3
Order By: Relevance
“…It is still not known whether bubbles found in the heart or carotid arteries are trapped in a sclerosant layer, or if they have any sclerosing activity [20]. Recent in vitro studies demonstrated that the detergent sclerosants polidocanol and STS are strongly neutralised by blood contact, mainly due to consumption and deactivation by circulating blood cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is still not known whether bubbles found in the heart or carotid arteries are trapped in a sclerosant layer, or if they have any sclerosing activity [20]. Recent in vitro studies demonstrated that the detergent sclerosants polidocanol and STS are strongly neutralised by blood contact, mainly due to consumption and deactivation by circulating blood cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Але в той же час не можна ігнорувати роботи в яких описується взаємодія склерозантів з компонентами крові в просвіті вени людини, що може кардинально впливати на кінцевий клінічний результат. Внутрішньо-судинне введення призводить до змішування склерозантів з кров'ю, зниження літичної та клінічної активності (Connor, Cooley-Andrade, Goh, Ma & Parsi, 2015). Історично нейтралізуючий ефект крові був пов'язаний з розведенням.…”
Section: вступunclassified
“…Історично нейтралізуючий ефект крові був пов'язаний з розведенням. Дослідники успішно оскаржили це поняття і продемонстрували, що розбавлення грає лише незначну роль у зниженні літичної активності склерозантів і що зв'язування з білками плазми і, зокрема, з альбуміном, надає більш значний вплив (Connor et al, 2015).…”
Section: вступunclassified
“…2,3,10 Polidocanol is one of the most common sclerosing agents used in human medicine, is most often used intravenously for treatment of uncomplicated spider and reticular veins, and has been used percutaneously to treat aneurysmal bone cysts. 10,[15][16][17][18][19][20] When injected intravenously, polidocanol causes rapid overhydration and destruction of endothelial cells in a concentration-and volume-dependent manner which leads to inflammation, platelet aggregation, fibrosis, and eventual occlusion of the vessel. 3,[17][18][19] Identified as a "tender sclerosant", polidocanol is well-tolerated, non-painful upon injection, and is often the sclerosant of choice for use near nerves or muscles.…”
Section: Introductionmentioning
confidence: 99%
“…10,[15][16][17][18][19][20] When injected intravenously, polidocanol causes rapid overhydration and destruction of endothelial cells in a concentration-and volume-dependent manner which leads to inflammation, platelet aggregation, fibrosis, and eventual occlusion of the vessel. 3,[17][18][19] Identified as a "tender sclerosant", polidocanol is well-tolerated, non-painful upon injection, and is often the sclerosant of choice for use near nerves or muscles. 15,[21][22][23][24] These desirable properties are likely a result of its original development as a long-acting local anesthetic.…”
Section: Introductionmentioning
confidence: 99%